A janus-faced manipulation: an investigation of narratives constructed on the Amazon in the target and source contexts - Etges, Christine Bareño (2000)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.